Demand-side Management in Territorial Entities based on their Volatility Trends - Dzyuba, Anatolyy; Solovyeva, Irina (International Journal of Energy Economics and Policy, 2019)
This article explores the issues of assessing electricity consumption by individual countries and territorial entities based on their demand volatility. The current demand-side management (DSM) programs deployed in different countries of the world do not take into account individual characteristics of energy demand, which affects their effectiveness. This article describes the methodology developed by the authors to analyze demand volatility in individual countries and territorial entities using a demand volatility map. The authors introduce new indicators for assessing the electricity demand volatility such as: “Annual Load Volatility Factor”, “Daily Load Factor” and “Demand Volatility Coefficient”, which underlie a demand volatility map. The map is used to identify similar demand volatility trends among individual countries and territorial entities and offer recommendations and management decisions for decreasing volatility in the grid on the level of individual countries and territorial entities. This article presents the results of testing the methodology in the form of two demand volatility maps – one built for the EU, the other for Russia. The EEC volatility map emphasized the need for a differentiated approach to demand-side management in different countries. It also allowed clustering the countries and revealed states with similar trends where similar DSM models could be deployed. The Russia-wide volatility map showed the regions that are best positioned for DSM and allowed the authors to produce recommendations on DSM for similar regional groups. The results of the study have high theoretical and practical importance which manifests in their potential application for the decision-making in the field of DSM in individual countries and territorial entities, aimed at reducing energy consumption and improving energy efficiency. Keywords: demand-side management, electricity consumption, energy efficiency, energy costs, energy cost management JEL Classifications: Q43, P18, L94 DOI: https://doi.org/10.32479/ijeep.8682